Some Implications of Legal Education Methods and their Reform - Pérez Perdomo, Rogelio (1982)
This article offers a constructive critique of traditional teaching methods in legal education, focusing especially on the “master class”, based on the unilateral transmission of knowledge by the teacher. In this regard, the author argues that this method does not promote effective retention or the development of appropriate mental habits for the legal profession; rather, it contributes to a “distortion” of jurists. Instead, he advocates a transformation in the pedagogy of law, using techniques that diminish the “one man show” and encourage active participation and the development of critical skills. This entails a shift in the role of the law teacher: from being a mere transmitter of information to being a facilitator and advisor of learning. While acknowledging the challenges associated with transitioning to a more participatory pedagogy, the author considers it essential to improve the training of lawyers and to adapt to the constant changes in the field of law.